Biological Concrete - Material of the Future in the Aral Region - Shinbergenovich, Seydullaev Suleyman; uli, Aytmuratov Amanbay Tuoelbay; Toxtarbayevna, Allambergenova Maxsuda (European Journal of Life Safety and Stability (2660-9630), 2022)
The article will tell about the technology of concrete, the classification of concrete for construction will be given and important aspects of the production of concreting of construction structures will be indicated.